Relationship marketing: Healthcare management programme at PMCare Sdn Bhd / Nazila Nor Said - Nor Said, Nazila (Faculty of Business and Management, 2006)
The objective of the study is to reach on the Relationship Marketing of Healthcare Management Programme in PMCare Sdn Bhd. The final report will help PMCare identify the perception of its customers, and if there are problems, that may cause dissatisfaction among the customers toward PMCare to extend, it affects the sales performance. Yet, Relationship Marketing strategies and tactics are context specific. this paper reports show how business relationships may develop in the future and the practices that should be used under certain scenarios. It concludes with recommendations of areas where further research activity in Relationship Marketing is required. Seeking knowledge of a customer's personal feelings concerning their comfort level with various communication approaches could enhance the reception of messages crafted for them. The discipline needs to move beyond the numbers to a more abstract analysis of the customer as an individual with specific feelings toward various marketing approaches.